2014
DOI: 10.4172/2167-0420.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Child (Early) Marriages among Young Girls- A Public Health Issue

Abstract: Abstract"The Sindh government has recently proposed amending the old child marriage laws to include stricter penalty and punishments". The practice of early marriage has increasingly been recognized as human rights violation affecting girls more than boys with severe consequences. Though the numbers of cases have reduced worldwide, it still remains pervasive in South Asia, predominantly in Pakistan. Despite national laws and international agreements, this public health issue presents a threat to the lives and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Parents may frequently believe that a young girl is a financial burden, which may PLOS ONE account for this. They, therefore, believe that marrying their young daughters will aid the poor family in terms of both social and financial rewards [74].…”
Section: Plos Onementioning
confidence: 99%
“…Parents may frequently believe that a young girl is a financial burden, which may PLOS ONE account for this. They, therefore, believe that marrying their young daughters will aid the poor family in terms of both social and financial rewards [74].…”
Section: Plos Onementioning
confidence: 99%
“…Daughters who were married would live separately from their families and live with their husbands, therefore, it would decrease the economic burden of their families. Inadequate income would also affect children's educational status which was low, resulting the children to have early marriage (Hotchkiss et al, 2016;Bhanji and Punjani, 2014).…”
Section: The Effect Of Family Income On the Incidence Of Early Marriagementioning
confidence: 99%
“…In many societies, cultural and ideological norms limit the roles and participation of women to that of their reproductive capacity and custodial duties. This is especially prevalent among poor families, where a girl is often perceived as an economic burden (Bhanji & Punjani, 2014). A South Indian study found that the education of girls is often undervalued because of the dominant cultural belief that a girl should be married off to live with her husband, who would work and provide income (Bhagavatheeswaran et al, 2016).…”
Section: Female Gender Expectationsmentioning
confidence: 99%